The Pot Rush: Is Legalized Marijuana a Positive Local Amenity? - Diego Zambiasi; Steven Stillman (Institute of Labor Economics (IZA), 2018)
This paper examines the amenity value of legalized marijuana by analyzing the impact of marijuana legalization on migration to Colorado. Colorado is the pioneering state in this area having legalized medical marijuana in 2000 and recreational marijuana in 2012. We test whether potential migrants to Colorado view legalized marijuana as a positive or negative local amenity. We use the synthetic control methodology to examine in- and out-migration to/from Colorado versus migration to/from counterfactual versions of Colorado that have not legalized marijuana. We find strong evidence that potential migrants view legalized marijuana as a positive amenity with in-migration significantly higher in Colorado compared with synthetic- Colorado after the writing of the Ogden memo in 2009 that effectively allowed state laws already in place to be activated, and additionally after marijuana was legalized in 2013 for recreational use. When we employ permutation methods to assess the statistical likelihood of our results given our sample, we find that Colorado is a clear and significant outlier. We find no evidence for changes in out-migration from Colorado suggesting that marijuana legalization did not change the equilibrium for individuals already living in the state.
Keywords: I18; R23; K42; C22; 330; marijuana legalization; interstate migration; synthetic controls